The Relationship Between Parental Supervision And The Use Of Smartphone On Children - Rina Putri; Jamaris Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research is motivated by the use of gadgets by children of SMP Angkasa Lanud Padang City is classified as not good, it is suspected that this is due to low parental supervision in the use of gadgets by children. This study aims to describe parental supervision, describe the use of children's gadgets, and see the relationship between parental supervision and the use of gadgets by children at SMP Angkasa Lanud Padang City.This type of research is quantitative while the approach used is correlational. The population in this study were all students using gadgets who attended SMP Angkasa Lanud Padang City totaling 144 people. While the sampling technique used the Simple Random Sampling technique, as many as 25% of the 144 students, namely 36 students. The data collection technique uses a questionnaire distributed to junior high school students, while the data analysis technique uses the Percentage and Product Moment formulas. The results of this study indicate that parental supervision is classified as low, the use of gadgets is classified as lacking, and there is a significant relationship between parental supervision and the use of gadgets by junior high school students. Suggestions, parents should supervise junior high school children who are carried out at night by controlling, educating, maintaining, guiding and evaluating.Keywords: Parental supervision, use of gadgets